Problem-Based Collaborative Learning Model Improves Physical Education Learning Outcomes for Elementary School Students - Endrawan, I Bagus; Aliriad, Hilmy (MIMBAR PGSD Undiksha, 2023)
The problems in this study included the low PE values obtained from the results of observations and student response questionnaires. This study aimed to analyze the effectiveness of problem-based collaborative learning models on the learning outcomes of Physical Education students in elementary schools. This study uses a quasi-experimental design. Methods of data collection using interviews, observation, and tests. The instruments used were learning achievement tests, learning observations, and student response questionnaires to learning. Data analysis techniques using descriptive qualitative analysis, quantitative, and inferential statistics. The study results included three aspects of assessment, namely the cognitive, affective, and psychomotor aspects, which had good averages, namely 3.4, 3.5, and 3.3, respectively. The standard deviation or variation of each aspect of the assessment is 0.5. Overall, student learning outcomes are also categorized as good, with an average of 3.4, an average score of 85, and a standard deviation of 0.5. The results of the relationship between collaborative learning and learning outcomes in PE subjects with a significance level of 0.05 indicates a significant relationship between the two. The results of hypothesis testing show that the collaborative model has a significant influence on learning outcomes. It was concluded that collaborative learning improves PE students' learning outcomes more effectively than conventional learning. Factors that can affect student learning outcomes include the learning environment, learning methods used, and the quality of teacher teaching.